Prognostic value of systematic lymphadenectomy in patients with ovarian cancer: A systematic review and meta-analysis. (December 2021) - AlMahdy, AlBatool M.; Elassall, Gena M.; Abdelbadee, Ahmed Y.; Abd-Elkariem, Ahmed Y.; Atef, Fatma; Ahmed, Islam A.; Sayed, Esraa G.; Salah, Mohamed Ashraf; Ali, Ahmed K.; Ragab, Esraa Y.; Abd Elazeem, Hossam Aldein S.; Saad, Mahmoud M.; et al.
Abstract: Objective: To appraise clinical outcomes of systematic lymphadenectomy in women with ovarian cancer based on stage, control group and type of chemotherapy. Study design: A literature search was conducted on SCOPUS, PUBMED, COCHRANE, MEDLINE, and WEB OF SCIENCE databases. All comparative studies that assess outcomes of systematic lymphadenectomy in patients with ovarian cancer were eligible. Overall survival was analyzed by pooling log hazard ratio (HR) and standard error of multivariable Cox regression models. MOGGE Meta-analysis Matrix is a novel illustration tool that was used to demonstrate multiple subgroup analyses of included studies. Results: Twenty-two studies were eligible. Systematic lymphadenectomy was associated with better overall survival, that was close to significance, compared to control group (HR 0.93, 95 %CI 0.86–1.00). Among women treated with adjuvant chemotherapy, overall survival improved in women with stage IIB-IV who underwent systematic lymphadenectomy (HR 0.91, 95 %CI 0.84−0.99) and was most significant among patients with stage III to IV (HR 0.85, 95 %CI 0.73−0.99). Systematic lymphadenectomy did not improve survival in women who received neoadjuvant chemotherapy (HR 0.97, 95 %CI 0.73–1.29). Systematic lymphadenectomy was associated with improved progress-free survival compared to control group (HR 0.88, 95 %CI 0.79−0.99). Conclusion: Although data from clinical trials do not support role of systematic lymphadenectomy in advanced ovarian cancer, overall data conveys stage-specific survival benefit. Further clinical trials may be warranted to assess substage survival outcomes in women with advanced stages.